Siğilmāsa : approche typo-technologique du bâti, processus de formation du site et gestion des matières premières - Romain Mensan; François-Xavier Fauvelle; Elarbi Erbati; Laurent Bruxelles (Mélanges de la Casa de Velázquez, 2017)
This article presents some findings from the French-Moroccan archaeological mission to Siğilmāsa. Given the poor preservation and visibility of the archaeological remains, which makes their interpretation particularly difficult, we first proposed a geomorphological study of the site. This was then completed by geoarchaeological test pits in order to better understand the topography of the site. The observation of two different qualities of «pisé», one orange and one gray, together with direct radiocarbon dating, suggests some technological evolution of the construction material and enables us to place it in a clear stratigraphic framework. Finally, we posited the existence of a relationship between the process of site formation and availability of the raw materials (gravel, loam, earth…) used in different pisés observed.